Quasar 3.0 - A Situational Approach to Software Engineering - Kremer, Marion; Engels, Gregor; Hofmann, Alexander; Hohwiller, Jörg; E. Nandico, Oliver; Nötzold, Thomas; Prott, Karl; Schlegel, Diethelm; Seidl, Andreas; Wolf, Thomas

Model-Based Testing: Achievements and Future Challenges - Mlynarski, Michael; Güldali, Baris; Weißleder, Stephan; Engels, Gregor (Advances in Computers)
Software systems are part of our everyday life and they become more complex day by day. The ever-growing complexity of software and high quality requirements pose tough challenges to quality assurance. The quality of a software system can be measured by software testing. However, if manually done, testing is a time-consuming and error-prone task. Especially test case design and test execution are the most cost-intensive activities in testing. In the previous 20 years, many automation tools have been introduced for automating test execution by using test scripts. However, the effort for creating and maintaining test scripts remains. Model-based testing (MBT) aims at improving this part by systematizing and automating the test case design. Thereby, test cases or automatable test scripts can be generated systematically from test models. MBT is already known for several years, but it currently gains a great momentum due to advanced tool support and innovative methodological approaches. This chapter aims at giving an overview of MBT and summarizes recent achievements in MBT. Experiences with using the MBT approach are illustrated by reporting on some success stories. Finally, open issues and future research challenges are discussed.

Automatische Kompatibilitätsprüfung Framework-basierter Anwendungen - Christ, Fabian
Software-Architekturen betrieblicher Informationssysteme bestehen aus Architekturbausteinen wie Frameworks, Komponenten und Bibliotheken. Die Entwicklung dieser Architekturen unter Einbeziehung wiederverwendbarer Architekturbausteine ist eine Voraussetzung einer industriell organisierten Software-Entwicklung. Für eine effiziente Trennung der Zuständigkeiten werden dabei häufig Architekturbausteine von Drittanbietern wiederverwendet.Frameworks als erweiterbare Architekturbausteine bieten besondere Vorteile. Sie erlauben sowohl die Wiederverwendung der Funktionalität als auch der durch das Framework vorgegebenen Software-Architektur. Beispiele sind Frameworks für Benutzungsoberflächen oder für die Anbindung von Datenbanken. Durch Implementierung anwendungsspezifischer Erweiterungen wird ein Framework für den konkreten Anwendungsfall angepasst. Eine Anwendung, deren Software-Architektur ein Framework einsetzt, benutzt das Framework über dessen Erweiterungspunkte.Im Laufe der Evolution einer solchen Anwendung entsteht häufig die Situation, dass das Framework durch eine neuere Version aktualisiert werden soll. Die Aktualisierung enthält das Risiko, dass Inkompatibilitäten zwischen bestehender Anwendung und neuer Framework-Version auftreten, die wiederum zu aufwendigen Anpassungen führen. Daher müssen mögliche Inkompatibilitäten vor der Aktualisierung erkannt und bewertet werden. Nach aktuellem Stand der Technik ist dies nicht möglich, so dass es in der industriellen Praxis zu unvorhergesehenen Problemen verbunden mit hohen Kosten kommt.Wir stellen ein Verfahren zur automatischen Kompatibilitätsanalyse Framework-basierter Anwendungen vor, mit dem das beschriebene Problem gelöst wird. Durch eine Kombination aus Codeanalyse und neuartiger Framework-Beschreibung lassen sich mögliche Inkompatibilitäten vor Durchführung der Aktualisierung automatisch berechnen. Eine prototypische Implementierung des Verfahrens im Werkzeug »Companian« demonstriert die praktische Einsetzbarkeit unseres Verfahrens.Für die Definition der benötigten Framework-Beschreibungssprache mittels Meta-Modellierung setzen wir die neuartige Modellierungstechnik der parametrisierten Meta-Modelle ein. Die Technik unterstützt unseren Ansatz einer anforderungsbasierten Wiederverwendung von Sprachen. Mit diesem Ansatz können bestehende Sprachen für Teilaspekte neu definierter Sprachen wiederverwendet werden. Unser pragmatischer Ansatz stellt dabei sicher, dass hierbei nur die Sprachen benutzt werden können, die syntaktisch und semantisch den geforderten Sprachen entsprechen.

Towards Rich Change Management for Business Process Models - Gerth, Christian; Luckey, Markus (Proceedings of the Workshop on Comparison and Versioning of Software Models (CVSM'12))

A UML-based Rich Service Description Language for Automatic Service Discovery of Heterogeneous Service Partners - Huma , Zille; Gerth , Christian; Engels, Gregor; Juwig, Oliver (Proceedings of the Forum at the CAiSE'12 Conference on Advanced Information Systems Engineering)

Modeling with Adapt Cases - Luckey , Markus; Mutz, Felix (Repository for Model-Driven Development (ReMoDD))

Ein Ansatz zur dynamischen Qualitätsmessung, -bewertung und Anpassung von Software Engineering Methoden - Geisen , Silke; Luckey , Markus; Engels, Gregor (Proceedings of 19. GI-WIVM Workshop: Qualitätsmanagement und Vorgehensmodelle)

Towards a Framework for the Integration of Modeling Languages - Arifulina, Svetlana (Proceedings of the Doctoral Symposium of the 5th International Conference on Software Language Engineering 2012, Dresden, Germany (SLE (Doctoral Symposium)))

Entwicklung eines Softwarewerkzeugs für die modellgetriebene Migration betrieblicher Informationssysteme - Güldali , Baris; Sauer, Stefan; Löhr, Perdita (Proceedings of the Workshop Modellbasierte und Modellgetriebene Softwaremodernisierung (MMSM 2012))

Assessing composition in modeling approaches - Mussbacher , Gunter; Alam , Omar; Alhaj , Mohammed; Ali , Shaukat; Amálio , Nuno; Barn , Balbir; Bræk , Rolv; Clark , Tony; Combemale , Benoit; Cysneiros , Luiz Marcio; Fatima , Urooj; France , Robert; et al. (Proceedings of the Workshop about Comparing Modeling Approaches 2012 (@MODELS 2012))

Multi-Staged Quality Assurance for Self-Adaptive Systems - Luckey , Markus; Thanos , Christian; Gerth, Christian; Engels, Gregor (Proceedings of 1st International Workshop on EVALUATION for SELF-ADAPTIVE and SELF-ORGANIZING SYSTEMS at SASO'12)

Ein Ansatz zur Anpassung von Software Engineering Methoden im laufenden Projekt - Geisen, Silke (Proceedings of Software Engineering 2012 (SE 2012) - Doktorandensymposium)

Partially Evaluating Finite-State Runtime Monitors Ahead of Time - Bodden, Eric; Lam, Patrick; Hendren, Laurie (ACM Transactions on Programming Languages and Systems)

Weaving-based configuration and modular transformation of multi-layer systems - Besova, Galina; Walther, Sven; Wehrheim, Heike; Becker, Steffen (Proceedings of the 15th International Conference on Model Driven Engineering Languages & Systems (MoDELS))
In model-driven development of multi-layer systems (e.g. application, platform and infrastructure), each layer is usually described by separate models. When generating analysis models or code, these separate models rst of all need to be linked. Hence, existing model transformations for single layers cannot be simply re-used. In this paper, we present a modular approach to the transformation of multi-layer systems. It employs model weaving to dene the interconnections between models of dierent layers. The weaving models themselves are subject to model transformations: The result of transforming a weaving model constitutes a conguration for the models obtained by transforming single layers, thereby allowing for a re-use of existing model transformations. We exemplify our approach by the generation of analysis models for component-based software.

Optimized XPath evaluation for Schema-compressed XML data - Böttcher, Stefan; Hartel, Rita; Heindorf, Stefan (ADC)

Generalizing and Improving SQL/XML Query Evaluation - Böttcher, Stefan; Bokermann, Dennis; Hartel, Rita (8th International Conference on Signal Image Technology and Internet Based Systems (SITIS'12))

Continuous Local Strategies for Robotic Formation Problems - Kempkes, Barbara; Meyer auf der Heide, Friedhelm (Experimental Algorithms)

Optimal and competitive runtime bounds for continuous, local gathering of mobile robots - Kempkes, Barbara; Kling, Peter; Meyer auf der Heide, Friedhelm (Proceedinbgs of the 24th ACM symposium on Parallelism in algorithms and architectures - SPAA '12)

Local, Self-organizing Strategies for Robotic Formation Problems - Kempkes, Barbara; Meyer auf der Heide, Friedhelm (Algorithms for Sensor Systems)

Faculty Submitted Student Work at Siggraph 2012 - Domik, Gitta (Curated exhibit at Siggraph)